Food Safety, Consumption and COVID-19: an Observational Study among University Students - Alvarez Ramírez, María Magdalena; Luzanía Valerio, Manuel Salvador; Ortiz Chacha, Christian Soledad; López Galindo, Lol Ki Itzel; Pérez Juárez, Miriam Celia (Horizonte Sanitario, 2023)
Objective: To determine the degree of security and food insecurity of university students and their homes in the period of the COVID-19 pandemic. Materials and methods: A cross-sectional, observational study was carried out with 110 university students from the faculty of nutrition in the Xalapa region of the Universidad Veracruzana (UV), through an online survey in which they reported individual information and information on their household members. The online survey was hosted on the platform of the survey system of the University Coordination of Observatories (CUO) of the UV and was applied during november 2020. Results: Due to the pandemic situation, half of the respondents reported that their food expenses decreased,this was also affected because, in this period, in 15.4% of households, between 1 and 2 household members lost their job or source of income. A prevalence of households in food safety of 82.72% was identified, 12.73% mild insecurity and 4.55% moderate insecurity; 83.6% of the households presented slight alterations in their diet; almost half (45%) maintained the same pattern of consumption of processed and ultra-processed foods. Conclusions: It is necessary to promote educational interventions in the university context that favor healthy habits of students and access to nutritious and varied products, and with this, seek better food safety. Key words: Food safety; COVID 19; Food consumption; Students.